2005
DOI: 10.1002/car.877
|View full text |Cite
|
Sign up to set email alerts
|

The child protection conference: A study of process and an evaluation of the potential for on-line group support

Abstract: The processes underpinning child protection decision-making have been less frequently studied than the consequences of decision outcomes. This paper reports the findings of three investigations into the dynamics and processes involved in reaching decisions about the registration of children as at risk. The three studies reflect an approach which is to triangulate onto the core of decision processes by focusing on different aspects of those processes. Study One reports the findings of a linguistic and discursiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
(8 reference statements)
2
17
0
Order By: Relevance
“…The concept of collective memory as a tool for sharing experiences between colleagues as emerged in several different interviews. Research conducted by Britner and Mossler (2002), Prince et al . (2005) and Kelly & Milner (1996) has emphasized the importance of intra‐professional decision‐making.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of collective memory as a tool for sharing experiences between colleagues as emerged in several different interviews. Research conducted by Britner and Mossler (2002), Prince et al . (2005) and Kelly & Milner (1996) has emphasized the importance of intra‐professional decision‐making.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…But the lack of evaluations and other more objective criteria to relate the discussion to, means that such decisions can be difficult and uncertain, giving much weight to the more influential actors as indicated by other research (e.g. Prince et al . 2005).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings resonate strongly with these observations. Akin to the findings of others, parents were intimidated by the large number of professionals in attendance and experienced the quasi-legal discursive practices which framed these meetings as intimidating and marginalising (Healy et al, 2011(Healy et al, & 2012Buckely, et al, 2011;Dale, 2004;Prince et al, 2005;Thomson & Thorpe, 2004). While parents fundamentally understood the functions of the case conference at the time of interview and discussed being informed about the nature and structure of case conferences, they also reported that this did not prepare them for the emotional impact of attendance:…”
Section: Child Protection Case Conferencesmentioning
confidence: 98%
“…The child protection register is a confidential record of the details of children who have been identified as being at risk and in need of a multiagency child protection plan. If the CPCC considers that the criterion for registration has been met, then the child will become subject to a child protection plan (Prince et al, ). Further CPCCs will then be held at regular intervals until the child is either removed into the care of the local authority or is no longer considered at risk of significant harm.…”
Section: Cpccs In Scotlandmentioning
confidence: 99%